Application of three‐dimensional reconstruction and visible simulation technique in reoperation of hepatolithiasis. Issue 2 (22nd January 2013) - Xie, Aowen; Fang, Chihua; Huang, Yanpeng; Fan, Yinfang; Pan, Jiahui; Peng, Fengping
Abstract Background and Aim Hepatolithiasis often requires repeated operations in East Asia. This study aims to evaluate the clinical application of three‐dimensional reconstruction and visible simulation techniques for repeated operation in patients with intrahepatic calculi. Methods A medical image processing system was used for modeling, segmentation, and three‐dimensional reconstruction of intrahepatic stones in 20 patients, consisting of 7 males and 13 females who were subjected to repeated surgical treatment from May 2010 to November 2011. The three‐dimensional models of the liver and bile ducts in a standard template library format were then processed by the FreeForm Modeling System. Accurate digital information about the bile duct system, lesions, calculi distribution, and surrounding organs obtained from all directions, multiple angles, and multistrata were used to decide the rational surgical modality. Virtual operations were then performed on the models with virtual surgical instruments in the FreeForm Modeling System. The results were used to guide and were compared with the real surgical procedures performed. Results The surgical outcomes of all patients in this study were satisfactory. Three‐dimensionally reconstructed models provided clear and strong relief perception and a user‐friendly interface. Visible simulation surgery performed based on three‐dimensionally reconstructed models led to an optimal operation plan that had great resemblance to the actual surgeries for cases with intrahepatic stones. Conclusions Three‐dimensional reconstruction and visible simulation techniques had unique value in optimizing repeated operation plans and in guiding actual surgical procedures for patients with recurrent intrahepatic calculi.